A correlation for predicting smoke layer temperature in a room adjacent to a room involved in a pre‐flashover fire. (20th December 2012) - Johansson, Nils; van, Patrick
SUMMARY Advanced fire modelling software have been developed and improved during the last couple of decays and these kinds of software have been shown to be valuable tools for fire safety engineers. However, the advances made have not replaced the need for simple hand‐calculation methods. Simple hand‐calculations methods can be used to obtain a first estimate of, for example, smoke layer temperatures in a performance‐based design or to help an engineer determine if it is necessary to perform a detailed computational fluid dynamics calculation, but the current hand‐calculations methods are limited. The current methods can for example only predict smoke gas temperatures in the fire room. A correlation that could predict temperatures in an adjacent space would be useful in performance‐based design when, for example, evaluating the conditions for evacuees or sensitive equipment in an adjacent space to the room of fire origin. In this paper, a correlation for predicting gas temperatures in a room adjacent to a room involved in a pre‐flashover fire is developed. The correlation is derived from results from computer simulations and the external validity is studied by comparing results from the correlation with full‐scale test data. Copyright © 2012 John Wiley & Sons, Ltd.